Genes for Cognitive Function: Developments on the X - Gécz, Jozef; Mulley, John

(untitled) (Genome Research, 2000)
Developments in human genome research enabled the first steps toward a molecular understanding of cognitive function. That there are numerous genes on the X chromosome affecting intelligence at the lower end of the cognitive range is no longer in doubt. Naturally occurring mutations have so far led to the identification of seven genes accounting for a small proportion of familial nonspecific X-linked mental retardation. These new data indicate that normal expression of many more X-linked and autosomal genes contribute to cognitive function. The emerging knowledge implicating genes in intracellular signaling pathways provides the insight to identify as candidates other X-linked and autosomal genes regulating the normal development of cognitive function. Recent advances in unravelling the underlying molecular complexity have been spectacular but represent only the beginning, and new technologies will need to be introduced to complete the picture.